Evaluation of antiasthmatic activity of Caesalpinia bonducella [L.] Roxb. seed - Khandagale, Prakash Devidas; Puri, Abhijeet V. (Journal of Drug Delivery and Therapeutics, 2019)
Objective: The study was planned to investigate the antiasthmatic activity of C. bonducella seeds by means of various in-vitro and in-vivo animal models. Methods: In the present study, petroleum ether and ethanolic extracts of C. bonducella seeds were evaluated for preliminary phytochemical screening and antiasthmatic activity in-vitro. Results: Preliminary phytochemical screening has revealed the presence of steroids, saponins, flavonoids, alkaloids, and tannins. Ethanolic extract of C. bonducella seeds exhibited antihistaminic activity at the dose of 50 and 100 mg/kg, it inhibited clonidine-induced catalepsy but not haloperidol-induced catalepsy. Ethanolic extract significantly inhibited increased leukocyte besides eosinophil count due to milk allergen moreover showed maximum protection against mast cell degranulation by clonidine. The results of guinea pig ileum indicated that the compound 2-methyl, 1-hexadecanol isolated from ethanolic extract significantly relaxed the ileum muscle strips that were pre-contracted. Conclusion: The present study concludes that the antiasthmatic activity of ethanolic extract C. bonducella seeds may be due to 2-methyl, 1-hexadecanol. Hence, a detailed study needs to be conducted to isolate phytoconstituents responsible for antiasthmatic activity accordingly their clinical efficacy in the treatment of related diseases. Keywords: C. bonducella, Phytochemical Screening, Antiasthmatic activity